Model Konseling Qalbun Salīm: Konstruksi Teoretis Berdasarkan Integrasi Ayat-ayat Penyucian Jiwa (Q.S. Asy-Syams: 9-10) dan Teknik Cognitive Behavioral Therapy (CBT): The Qalbun Salīm Counseling Model: A Theoretical Construction Based on the Integration of the Verses of Soul Purification (Q.S. Asy-Syams: 9-10) and Cognitive Behavioral Therapy (CBT) Techniques - Kholisin, Addin (RABBAYANI: Jurnal Pendidikan dan Peradaban Islami, 2025)
This article aims to construct an integrative counseling model "Qalbun Salīm" through a conceptual study combining the concept of soul purification (tazkiyatun nafs) in Q.S. Asy-Syams: 9-10 with Cognitive Behavioral Therapy (CBT) techniques. Using an integrative-philosophical approach involving Quranic hermeneutics and conceptual synthesis, this study yields a theoretical model with four pillars: spiritual awareness (al-waʿī), tawhid-based cognitive restructuring, directed behavioral change (al-ʿamal al-ṣāliḥ), and continuous evaluation (muḥāsabah). This model offers a coherent framework for counseling practice sensitive to Islamic culture and spirituality, while contributing to the enrichment of Islamic psychology and the expansion of cross-cultural CBT perspectives. Implications include recommendations for empirical research to validate the model and develop counselor training modules integrating clinical competence with spiritual understanding